Hudson Strait Inflow: Structure and Variability. Issue 9 (7th September 2021) - Ridenour, Natasha A.; Straneo, Fiammetta; Holte, James; Gratton, Yves; Myers, Paul G.; Barber, David G.
Abstract: Hudson Strait is the main pathway of heat, mass, and freshwater exchange between Hudson Bay and the Arctic and North Atlantic oceans. The outflow along the southern coast of the strait, a fresh, baroclinic jet directed toward the North Atlantic, has received more attention due to its potential impact on deep convection in the Labrador Sea. However, details about the westward, more barotropic inflow along the northern coast of Hudson Strait remain unknown due to a scarcity of observations. Hudson Strait inflow waters affect the physical and biogeochemical systems of the bay, as well as the marine ecosystem, which supports the livelihoods of many Indigenous communities surrounding the Hudson Bay region. Here, we address this knowledge gap by analyzing data from two hydrographic surveys and four moorings deployed across the strait from 2008 and 2009. Three moorings were deployed on the northern side of the strait to map the inflow, and one was deployed on the southern side of the strait to capture the outflow. Along the southern side, a stratified, fresh outflow was observed, consistent with earlier studies. Along the northern coast, the inflow is weakly stratified and more saline, with seasonal changes distributed throughout the water column. Source waters of the inflow stem mainly from Arctic Water in the Baffin Island Current. A comparison with historical data suggests that after modification in western Hudson Strait, part of the inflow enters northern Hudson Bay to become deep water in the bay. Plain Language Summary: Hudson Strait is the gateway that connects Hudson Bay to the Arctic and North Atlantic oceans. Arctic Waters (AWs) flow into the bay via Hudson Strait, mixing with other waters in the region before being exported through the strait to the North Atlantic. Waters that flow into the bay along the northern Hudson Strait coast support the ecosystem, which is a food source for the local Indigenous communities, and affects the current system within the region. We present year‐long data from the northern side of Hudson Strait for the first time. On the southern coast, low salinity waters that have mixed with river waters in Hudson and James bays quickly flows out of the bay, as earlier studies have found. The current along the northern side of the strait, however, is slow, warm, and salty. Over the course of the year, wintertime cooling as well as changes in current speed occur throughout the water column. These Hudson Strait inflow waters are comprised of AWs flowing from Davis Strait. We estimate that almost half of the AW flowing south from upstream enters Hudson Strait, possibly weakening large low salinity flows that could impact the large‐scale global ocean circulation. Key Points: The first year‐round observations of the Hudson Strait inflow shows a weakly stratified and saline flow with little seasonality Inflow source waters stem from the Baffin Island Current and are mainly comprised of Arctic Water A portion of Hudson Strait inflow flows into Hudson Bay and is transformed into Hudson Bay deep water